A randomised comparison trial to evaluate an in-home parent-directed drug education intervention - Beatty, Shelley Ellen (Curtin University, 2003)
The long-term regular use of tobacco and hazardous alcohol use are responsible for significant mortality and morbidity as well as social and economic harm in Australia each year. There is necessary the more cost-efficient primary prevention strategies are equally, if not more important. Youth have been identified as an important primary prevention target group in public health initiatives designed to reduce drug-related harm. Strengthening parents' capacity to reduce children's risk of alcohol, tobacco and other drug-related harm is also recognised as an important strategy. The first chapter of this thesis introduces this public health issue, provides a summary of the present state of play regarding parent-training intervention research, and presents the research hypotheses. A comprehensive review of the epidemiological, empirical, and theoretical literature pertaining to this research is presented in Chapter 2. Recreational alcohol, tobacco and other drug (ATOD) use results in some 23 000 deaths (representing around 18% of all deaths) and the premature loss of some 160 000 person-years of life each year in Australia. The social consequences have been estimated to cost the Australian community almost $19 billion annually. The prevalence of young people in these data is also cause for concern. In Western Australia (WA), nearly one third of the alcohol-related deaths in the period 1993-1995 occurred in people aged less than 25 years. In 1995 in WA, alcohol use was responsible for almost two thirds of all drug-related deaths in those aged 15-34 years. Furthermore, road crashes accounted for almost half (45%) of the deaths among those aged under 25 years in WA and alcohol was a leading factor in these crashes. There is agreement that the use of ATODs is a learned behaviour and therefore broadbased psychosocial theories offer the most promising explanation for its onset.Recent research addressing adolescent ATOD-use initiation has focused on the concepts of adolescent vulnerability and resilience. This Social Development Model identifies several social factors that are posited to predict or be protective of ATOD use (and other hazardous behaviours) during childhood and adolescence. While parents are not the only social influence on children, they provide the primary social learning environment for children and as such, can play an important role in whether or not their children initiate ATOD use. Four major groups of parenting risk and protective factors are evident from the literature. These include parental modelling of ATOD use, the normative standards parents set regarding ATOD use, their parenting style and family management techniques, and the nature of parent-child communication. The provision of skills training consistent with the concepts of 'authoritative parenting' is supported in the literature as a means to reduce the likelihood of children engaging in hazardous behaviours. Such training is promoted as being an effective and enduring strategy for reducing youth behaviours, such as regular use of tobacco and hazardous use of alcohol and/or other drugs, that have the potential to cause substantial health, social, and financial harm. Few ATOD programs focussing on parenting skills (particularly parent-child communication) were found to have been subjected to rigorous efficacy or effectiveness studies. Of those subjected to empirical investigation, most were constrained by methodological shortcomings and/or difficulties in recruiting and maintaining substantial parent participation.Seeking ways to recruit and engage a high percentage of Australian parents in such a program is an important area for investigation because, while they may be difficult to reach, parents have persuasive and powerful influences on children's health behaviour. Potential predictors of parental participation were identified in the literature and a consultation process with parents was undertaken to determine their needs and preferences as well as strategies to recruit and engage a greater proportion of parents. The methodology of this research therefore comprised a small Exploratory Study followed by a larger efficacy trial. The Exploratory Study involved consultation with eight small groups of parents regarding the design and content of an ATOD educational intervention. The methodology of this consultation is presented in detail in Chapter 3. A questionnaire and structured group discussions of parents' responses were used to collect quantitative and qualitative data regarding their opinions and preferences regarding the frequency, intensity, time and type of an ATOD-related educational intervention. The results of the consultation with parents and a concurrent discussion of how each finding relates to previous research are presented in Chapter 4. Of the 213 parents/guardians invited, 110 responded, of which 72 indicated they would attend one of the discussion groups. While the attendance at the discussion groups was very low (response rate of 24% n=51), the total number of parents consulted exceeded or was equivalent to similar formative research.Parents reported they worry about the potential harm associated with ATOD use by children and probably underestimate their own children's vulnerability and ATOD-use experiences. They wanted to be involved in the planning phases of parent-oriented ATOD-related educational interventions. Parents also identified numerous barriers for their participation in educational programs. They identified flexibility and convenience regarding intervention delivery as being essential and preferred interventions to be home-based. The parents reported that any intervention directed at parents should be supported by parents, non-judgemental, simple, time-efficient, easy to use, fun, colourful and interactive. Parents recommended that practical communication skills (such as how to talk with children, how to raise the topic and what topics to talk about) be addressed in the intervention. Parents also recommended a range and combination of strategies to promote and maintain parent involvement, such as rewarding children of parents who participate. The second part of this research involved merging the exploratory data with information from previous similar research to develop a drug-related educational intervention for parents. A parent-directed ATOD educational intervention, designed to assist parents to talk with their Year 6 children about smoking cigarettes and drinking alcohol, was developed and implemented. Its feasibility and impact on parent-child drug-related communication were evaluated in a randomised comparison trial. The methods utilised in this trial are detailed in Chapter 5. Seven data collection instruments were developed and standardised data collection procedures were established. Demographic, process and impact data were collected. Schools were randomly selected and randomly assigned to one of three study conditions.Parents were recruited from schools. Intervention-group 1 was given a choice of learn-at-home drug education materials and Intervention-group 2 received learn-at-home drug education materials but were not given a choice. The Comparison-group parents were not exposed to the intervention. Completeness of the dissemination and implementation of the intervention were assessed, as were dose-response effects. Validity analyses of the parent-directed intervention indicated that the theoretical domains were adequately covered and the messages intended for parents were unambiguous. The student and parent questionnaires were also found to be valid and reliable. Data were obtained from 69.1% (n=830) and 24.5% (n=294) of the study sample (n=1201) at the first and second follow-ups respectively. Sample parents were successfully identified at both follow-ups and parent-child communication data were accurately matched (Chapter 6). At the first follow-up parents in Intervention-group 1 were more likely than parents in the Comparison Group, to have ever talked with their Year 6 child about smoking cigarettes; talked more recently; reported high parent-child engagement during such communication; and to have talked about more of the four specified tobacco-related topics in the two weeks prior to data collection. In addition, there were positive dose-response relationships for these dependent variables. While there were no significant differences between study conditions (Intervention- group 2 versus Comparison Group was marginally significant) regarding the duration of the last parent-child discussion about smoking cigarettes, there were positive dose-response effects.Likewise, compared to Comparison-group parents, those in Intervention-groups 1 and 2 were more likely to have ever talked with their Year 6 child about drinking alcohol at the first follow-up, to Comparison-group parents, those in Intervention-group 1 were also more likely to have talked with their Year 6 children more recently about drinking alcohol. Parents in both of the Intervention Groups were more likely than parents in the Comparison Group, to have reported: talking about drinking alcohol for a longer duration; having higher parent-child engagement during such communication; and talking about more of the three nominated alcohol-related topics. Additionally, there were positive dose-response relationships for the alcohol-related dependent variables. Furthermore, while dose-response effects were evident between the high and/or middle intervention-dose categories and the low-dose category, there were no differences between the middle and high categories for any of the dependent tobacco- or alcohol-related dependent variables. No statistically significant differences were found between the responses of parents who were offered a choice of intervention materials (Intervention-group 1) and those who were not (Intervention-group 2). The overall agreement between parents and their children to equivalent parent-child communication variables, at both baseline and first follow-up was low. Furthermore, the range of parent-child agreement between the items varied considerably. At the first follow-up, however, there appeared to be slightly increased levels of agreement between Intervention-group parents and their children, than there was between Comparison-group parents and their children.At the second follow-up the proportion of parents who had talked about none of the specified tobacco-related topics was low but there were no significant differences between the study conditions. There were, however, significant differences in the intended direction between study conditions with regard to how many of the specified alcohol-related topics parents reported discussing with their children. The likelihood of Type III error appeared to be minimal and indicators of parent and intervention itself and The findings of this study, discussed in Chapter 7, support the conclusion that parents of 10-11 year-old children are receptive to participating in a home-based drug-related educational intervention. The learn-at-home drug-related educational intervention implemented in this study appeared to have a significant impact on their drug-related communication with their Year 6 children. This study also identified strategies to enhance the recruitment and retention of participants in parent-training interventions, which are challenges inherent in parent-based intervention research. Despite identified limitations, this intervention appears to be a promising approach in the primary prevention of ATOD-related problems in Australia.